Softlifting in College: Cheating or Forgiving - Soni Agus Irwandi; Diyah Pujiati; Riski Aprilia Nita; Nanang Shonhadji; Syaifana Nabilah; Hafizd Oktariawan Maulana (Universitas Hayam Wuruk Perbanas, 2023)
Softlifting in higher education occurs due to the academic community's requirements and the convenience of accessing and downloading software through internet platforms. This research aims to investigate the impact of ethics sensitivity, moral ethics, perceived risk, perceived benefits, and habit on the intention to engage in softlifting. The study employed quantitative research through distributing questionnaires to accounting students at private universities in Surabaya. Data analysis was conducted using Structural Equation Model Partial Least Square (SEM-PLS). The findings reveal that ethics sensitivity, moral ethics, perceived risk, and habit have a negative and significant influence on the intention to engage in softlifting. On the other hand, perceived benefits have a positive and significant effect on softlifting intention. Incorporating ethical and moral values as research variables is an essential ethical consideration for those involved in software piracy, which adds originality to this study. This research emphasizes the importance of effective socialization and education against using pirated software or engaging in softlifting within the university environment. Furthermore, it underscores the responsibility of university management to provide legal software to students, which serves as a practical contribution to the overall issue.